2020
DOI: 10.21037/atm-20-1175
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA-based predictive biomarkers in breast cancer clinical trials: a narrative review

Abstract: Breast carcinoma is the most frequent and the second leading cause of cancer mortality in women worldwide. Current treatment decisions are based on tumor profiling of the initial tissue biopsy.Cancer though evolves both spatially and temporarily in a significant percentage of patients during treatment. However, sequential biopsies from the primary tumor or its metastatic sites are not either convenient or feasible in the majority of cases. In the era of precision medicine, analysis of circulating bloodbased bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…LB of body fluids is commonly used for the diagnosis of multiple human diseases [36,37]. Although miRNAs have been widely assessed as biomarkers in body fluids [38,39], it was recently reported that circRNAs are highly resistant to RNA degradation by exonucleases compared with miRNAs [4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…LB of body fluids is commonly used for the diagnosis of multiple human diseases [36,37]. Although miRNAs have been widely assessed as biomarkers in body fluids [38,39], it was recently reported that circRNAs are highly resistant to RNA degradation by exonucleases compared with miRNAs [4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes in the molecular profiles of primary tumours and metastasis can be longitudinally studied via a non-invasive and real-time approach [ 53 ]. Various trials have demonstrated the benefits of combined CDK4/6 inhibitors plus endocrine therapy in HR+/HER2− mBC, such as increasing the PFS, regardless of menopausal status, prior therapies, endocrine sensitivity, and the site of metastasis [ 23 , 60 ]. However, certain limitations remain to be resolved, such as the lack of predictive biomarkers with which to select patients or detect resistance [ 24 ]; these are among the current topics in the context of luminal metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary results show that ESR1 mutations were uncommon in patients that were not treated with AI in the neoadjuvant setting. In addition, a one-month treatment with palbociclib and AI decreased the ESR1 mutation rate [ 60 , 61 ].…”
Section: Circulating Tumour Dna (Ctdna) Analysis As a Tumour Biomarker In Hr+/her2− Mbc Patientsmentioning
confidence: 99%
“…Liquid biopsy provides an insight into the dynamic molecular profile of the primary tumour and its metastasis in a non-invasive and real-time approach [54]. A great variety of trials have demonstrated the benefits of combined CDK4/6 inhibitors plus endocrine therapy in HR+/HER2-MBC, such as increasing PFS regardless of menopausal status, prior therapies, endocrine sensitivity and type of metastasis [24], [57]. However, certain limitations were not resolved such as lack of predictive biomarkers to select patients or to detect resistance [25] and is one of the current topics in the context of luminal metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As preliminary results, ESR1 mutations were uncommon in patients no-treated with AI in the neoadjuvant setting. Besides, one-month treatment with palbociclib and AI decreases ESR1 mutation rate [57], [58].…”
Section: Circulating Tumour Dna (Ctdna) Analysis As a Promising Tumour Biomarkermentioning
confidence: 97%